A [Non]realistic Portrait of the Half-deaf Tonka by August Cesarec - Pieniążek-Marković, Krystyna (Poznańskie Studia Slawistyczne, 2020)
In the centre of the article’s interest, there are the expressionist ideas present in the work by Croatian writer from the inter-war period (1893–1941). The mini-novel/novella in question entitled Tonkina jedina ljubav (1931) is considered the work belonging to the epoch of the new/social realism which dominated in the 1930s, however, the author, as is shown on the basis of the article’s research, did not managed to free himself from influence of expressionism that shaped the most Croatian consciousness as for the avant-garde historical time (1910–1930). Focusing attention on a disabled woman along with her small-town environment of Zagreb before the World War I, the author draws her exaggerated, cartoonish portrait which has little to do with the realistic and mimetic reflection of reality. The work is a kind of aesthetic and ethical provocation, and serves as unmasking the idyllic image of Zagreb which turns out to be a city inhabited by intolerant and narrow-minded society convinced, however, of its civilisation superiority. The titular character is a victim of this society, and at the same time she remains its part. The aesthetic and ethical provocation concerns the disabled woman together with „inefficient” society living in the terrifying city.